Pembentukan Percontohan Sekolah Gigi Sehat Di SD Inpres Liliba Sebagai Upaya Meningkatkan Perilaku Pemeliharaan Kesehatan Gigi Dan Mulut Anak Usia Sekolah Dasar - Variani, Ratih; Krisyudhanti, Emma; Fankari, Ferdinan; Wali, Agusthinus (Universitas Islam Negeri Sumatera Utara, 2023)
Situation Analysis: Almost more than 50% of students in elementary school dental are dental workers so it is felt that there is a need for prevention with the establishment of healthy dental schools. And for + 2 years have not received dental health services / UKGS due to the Corona pandemic situation. Objective: Improve the behavior of elementary school-age children in maintaining dental and oral health and increase teacher understanding in filling out healthy dental cards and dental health education as the beginning of the formation of healthy dental schools. Community Service Method: PKM Approach Method with Participatory Action Research. This activity will be carried out at SD Inpres Liliba from April to October 2023, with participants being teachers and students of grades III and IV. Activity Results: Activities were carried out on grade 3 and 4 students totaling 50 children. First, students filled out a dental health maintenance behavior questionnaire before counseling, the results were included in the moderate criteria as many as 38 people (76.0%), teacher training on good and correct brushing practices, filling out healthy dental cards, and dental health education. The evaluation was carried out after 3 months, where there was an increase in behavior including the good category as many as 48 people (96.00%), teacher understanding in filling out healthy dental cards, dental health education and brushing practices were good and healthy dental schools had begun with brushing activities together every 1 week 1 time. Conclusion: This healthy dental school activity can improve the behavior of elementary school-age children in maintaining dental health and teachers' understanding is good in filling out healthy dental cards and teaching brushing and dental health education to students.